Myocarditis associated with Salmonella enterica serovar Weltevreden gastroenteritis in medical practitioner; case report from South India - Mahadevaiah Neelambike Sumana; Morubagal Raghavendra Rao; Vidyavathi B. Chitharagi; Badveti Satyasai; Supreeta R. Shettar; Veerabhadra G. S. Swamy; Chinchana S. Eshwarappa; Yogeesh D. Maheshwarappa (Frontiers in Medicine)
Salmonella enterica serovar Weltevreden, a non-typhoidal serovar, has emerged as a significant foodborne pathogen, particularly in Southeast Asian countries. While it is commonly associated with gastroenteritis and foodborne outbreaks, it can also lead to invasive infections in immunocompromised adults and neonates. This case report presents a rare instance of myocarditis associated with Salmonella Weltevreden gastroenteritis in a 43-year-old healthy male physician from South India. The patient had a month-long history of intermittent fever, which worsened 2 days before admission, along with myalgia and headache. A day after the admission the patient developed diarrhea. Upon investigation, stool culture revealed Salmonella enterica serovar Weltevreden. Notably, the patient had a genetic predisposition to inflammatory bowel disease and reported recent use of nonsteroidal anti-inflammatory drugs, which may have increased his susceptibility to non-typhoidal Salmonella infection. The patient also developed myocarditis, making this the first reported case of Weltevreden-associated myocarditis in the region. Antimicrobial susceptibility testing indicated ciprofloxacin susceptibility, an increasingly rare finding, as most reported serovar Weltevreden cases exhibit ciprofloxacin resistance. The patient recovered following treatment with ciprofloxacin and was discharged with instructions for follow-up. This case highlights the need for heightened awareness of the potential for non-typhoidal Salmonella infections to cause systemic manifestations, even in individuals without major underlying comorbidities. Continuous monitoring of antimicrobial resistance patterns and strict food safety measures are essential to control outbreaks of these emerging pathogens.